The conservation of a gender fantasy: women and Top 40 radio in Montreal - Maki, Christine (Université McGill, 2008)
This work examines today's Anglophone Top 40 radio in Montreal in terms of gender. Looking at the history of commercial radio, and the historical relationship between radio and women, it argues that these radio stations have always programmed based on an imagined rather than actual understanding of their target audience. Programmers today continue to hold a conservative understanding of their female audience and their interests, and to program using a stereotypical understanding of gender.

Imaginary Women, Imaginary Audience: Gender and Top 40 Radio in Montréal - Maki, Christine (Women in Radio: Unfiltered Voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audi ence. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit wom en’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.